Pengaruh Penggunaan Alat Permainan Edukatif “Taman Bunga Berhitung” terhadap Perkembangan Matematika Anak Usia Dini pada Kelompok B di TK Nurul Ikhlas Kota Bandung - Heri Hidayat; Fadilla Ayuningtyas; Dini Septi Ayu Sriwahyuni; Elsa Fitria Salsabila; Rahmi Fauziyah Nursafitri (Lembaga Yasin AlSys, 2026)
Numerical operation ability is an important aspect of early childhood numeracy development, but observations at TK Nurul Ikhlas Kota Bandung showed that some children aged 5–6 years still had difficulty understanding simple addition and subtraction concepts because learning had not optimally involved concrete media. This study aimed to determine the effect of using the Educational Play Equipment (APE) “Berhitung di Taman Bunga” on the numerical operation ability of children aged 5–6 years. This study used a quantitative approach with a One Group Pretest-Posttest Design. The research subjects consisted of 15 children from Group B of TK Nurul Ikhlas, selected using a total sampling technique. Data were collected through observation and analyzed using a normality test and a Paired Sample t-Test with the assistance of SPSS 25.0. The results showed that the mean score of numerical operation ability increased from 15.00 in the pretest to 21.67 in the posttest, with an improvement percentage of 44.47%. The Paired Sample t-Test results showed a significance value of 0.000 (< 0.05), indicating a significant effect of using the APE “Berhitung di Taman Bunga” on children’s numerical operation ability. The conclusion of this study confirms that the APE “Berhitung di Taman Bunga” is effective in improving simple addition and subtraction abilities in early childhood. These findings imply that game-based learning media and concrete objects can serve as relevant pedagogical alternatives to support children’s numeracy development in the foundational phase.